2022
DOI: 10.1155/2022/8924028
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Student Academic Performance at Higher Education Using Data Mining: A Systematic Review

Abstract: Recently, educational institutions faced many challenges. One of these challenges is the huge amount of educational data that can be used to discover new insights that have a significant contribution to students, teachers, and administrators. Nowadays, researchers from numerous domains are very interested in increasing the quality of learning in educational institutions in order to improve student success and learning outcomes. Several studies have been made to predict student achievement at various levels. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The approach aimed to predict student academic performance at a higher education level. Alwarthan et al's (2022) study identified an ensemble classification model that employed a Random Forest Ensemble with a dataset sourced from educational institutes' repositories. The study highlighted the scarcity of research predicting student academic performance in arts and humanities majors using students' data.…”
Section: Frequently Modeled Conventional Ensemble Classifiermentioning
confidence: 99%
“…The approach aimed to predict student academic performance at a higher education level. Alwarthan et al's (2022) study identified an ensemble classification model that employed a Random Forest Ensemble with a dataset sourced from educational institutes' repositories. The study highlighted the scarcity of research predicting student academic performance in arts and humanities majors using students' data.…”
Section: Frequently Modeled Conventional Ensemble Classifiermentioning
confidence: 99%
“…A student's academic efficacy is contingent upon the calibre of the instruction and learning process. To enhance this process, it is possible to utilize learning outcomes to assess and improve [5].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the testing dataset evaluates the performance of the constructed model from the trained data. In most cases, data is split into 70% for training EDM models, while 30% is used for model testing, where the accuracy of models is calculated (Alwarthan et al, 2022).…”
Section: Student Development Environmentmentioning
confidence: 99%
“…If the evaluation metrics are unmet, the evaluation stage produces feedback for stakeholders to adjust the selected features to improve model performance. The accuracy, recall, precision, ROC area, and F-score are some of the evaluation metrics used in EDM (Alwarthan et al, 2022). If the evaluation criteria are met, a model is built and used to predict the outcomes from student data.…”
Section: Student Development Environmentmentioning
confidence: 99%
See 1 more Smart Citation